Diversity and biomass of Chironomidae (Diptera) larvae in an impacted coastal lagoon in Rio de Janeiro, Brazil - CALLISTO,M. (2002)
Diversity and biomass of Chironomidae larvae were studied between January-November 1993 and March-November 1994 in an impacted lagoon in Rio de Janeiro, Southeastern Brazil, in an attempt to establish the ecological consequences of anthropogenic eutrophication processes. Nine hundred and seventy-five organisms belonging to the Tanypodinae, Orthocladiinae, and Chironominae were collected. Polypedilum (62%) and Chironomus (58%) were the most common genera found in the limnetic and littoral zones.